Scaling Roadmap: Site-Specific Fertilizer Recommendations (SSFR) through NextGen Advisory Platform in Ethiopia - Ewell, Hanna; Tibebe, Degefie; Mesfin, Tewodros; Makonnen, Brook T.; Ambaw, Gebermedihin; Solomon, Dawit; Girvetz, Evan (Accelerating Impacts of CGIAR Climate Research for Africa, 2025)
Key messages: